Primary aldosteronism: adrenalectomy could save more lives - Carling, Tobias; Faucz, Fabio R. (Frontiers in Endocrinology, 2025)
Primary aldosteronism (PA), a leading cause of secondary hypertension, remains profoundly underdiagnosed and, contributes to vast preventable cardiovascular morbidity and mortality worldwide. Affecting 4.5–20% of patients with high blood pressure, PA drives excess aldosterone production, substantially elevating risks of heart failure, stroke, atrial fibrillation, and renal damage, with untreated cases facing 10–20% higher mortality rates over 5–10 years compared to essential hypertension. Adrenalectomy for unilateral PA driven by somatic mutations (e.g., KCNJ5) offers markedly superior outcomes over medical therapy, yielding an absolute risk reduction in all-cause mortality that rivals or exceeds many major cardiovascular surgeries and greatly improves quality of life by resolving hypertension, hypokalemia, and associated symptoms. Advanced surgical approaches such as mini back scope adrenalectomy (posterior retroperitoneoscopic) minimize risks and enable precise, function-preserving surgery. Yet, current surgical rates, ranging from 1.2 to 8.4 per million across countries like Sweden, Taiwan, France, UK, Germany, and USA, represent less than 4% of the optimal rate of 212 operations/million. Achieving optimal adrenalectomy rates requires increasing surgical capacity 25–170-fold, potentially saving 5,627 lives annually in the USA alone. Disparities arise from diagnostic barriers, including underutilization of aldosterone-to-renin ratio screening, complex confirmatory testing, and limited access to adrenal vein sampling and high-volume adrenal surgeons. This perspective highlights PA’s severe burden, compares adrenalectomy’s efficacy to major cardiac and vascular operations, and examines international caseload variations linked to research infrastructure, PA guidelines, and access to high-volume centers. We strongly urge enhanced PA screening, improved case detection, diagnostic workflows, and expanded surgical access to avert this silent epidemic.